The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.15586/ijfs.v33isp1.2088
|View full text |Cite
|
Sign up to set email alerts
|

Underutilized horse chestnut (Aesculus indica) flour and its utilization for the development of gluten-free pasta

Abstract: There has been a growing demand for the production of gluten-free products due to increased occurrence of celiac disease. Thus, different research groups have been investigating the use of various available materials for the development of these functional products to fulfill customer’s needs. Horse Chestnut (Aesculus indica) seeds are underutilized, low-cost, and gluten-free, found in hilly areas of the Himalayan region of Kashmir valley, India. To determine their potential as an alternative to conventional f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 57 publications
(66 reference statements)
1
3
0
Order By: Relevance
“…The RS of the cultivars of this study was similar to that reported previously in plantain starch before cooking (87.50%), native GBF starch (88.70%), 53 and uncooked native plantain starch (85.00%), and 32 . A high RS content is associated with health benefits such as improved gut and digestive health 54 . Other benefits of RS include helping with weight loss and improved insulin sensitivity 55,56 .…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…The RS of the cultivars of this study was similar to that reported previously in plantain starch before cooking (87.50%), native GBF starch (88.70%), 53 and uncooked native plantain starch (85.00%), and 32 . A high RS content is associated with health benefits such as improved gut and digestive health 54 . Other benefits of RS include helping with weight loss and improved insulin sensitivity 55,56 .…”
Section: Resultssupporting
confidence: 84%
“…32 A high RS content is associated with health benefits such as improved gut and digestive health. 54 Other benefits of RS include helping with weight loss and improved insulin sensitivity. 55,56 Even though micronization slightly decreased the RS content of the GBF here, it is important to mention that the RS of micronized GBF remained relatively high.…”
Section: Ftir Of Micronized Gbfmentioning
confidence: 99%
“…Despite the absence of gluten proteins, GFM is characterised by the presence of hydrocolloids (in this case psyllium fibre, guar gum, hydroxypropyl‐methylcellulose) that are responsible for the formation of a gel‐like network during cooking (Marti & Pagani, 2013). Thus, the lowering of these ingredients in the formulation due to the addition of CF may be related to the formation of a less organised network that could promote a higher amount of solids lost in the cooking water (Gasparre & Rosell, 2019; Rafiq et al., 2021). In particular, it is worth considering that CF is generally characterised by a high presence of fibres and sugars (Dall'Asta et al., 2013; Demirkesen et al., 2014) that these components may have competed for the network hydration and would be responsible for weakening the pasta structure (Marti et al., 2010; Phongthai et al., 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Genetic susceptibility factors play a significant role in the development of celiac disease, an autoimmune condition that may cause significant intestine damage. In the general community, celiac disease affects 0.5% to 1% of people (Giménez‐Bastida et al, 2015 ; Manikantan et al, 2022 ; Rafiq et al, 2021 ). Contrarily, gluten sensitivity and/or other wheat proteins is caused by IgE antibodies that identify epitopes from certain proteins, known as allergens, setting off a chain of events that results in allergic inflammation.…”
Section: Introductionmentioning
confidence: 99%